Pengaruh Motivasi Kerja dan Budaya Organisasi terhadap Kinerja Karyawan Pada Transmart Carrefour Dutamall Banjarmasin di Masa Pandemi (Covid-19) - Widya Karina; Irwansyah Irwansyah (JURNAL BISNIS DAN PEMBANGUNAN, 2022)
ABSTRACT Every firm faces obstacles in a variety of conditions that might have an impact on the organization. As an example, consider the current epidemic, which impacts all industries and has an influence on economic globalization. As a result, the firm must be able to reduce losses, and one that influences the quality of human resources is defined by employee performance. The purpose of this study was to determine how work motivation and organizational culture affected employee performance at Transmart Carrefour Dutamall Banjarmasin during the Pandemic Period (Covid-19). Either partially or concurrently. A descriptive quantitative technique is used in this sort of study.The subjects of this research were employees of Transmart Carrefour Dutamall Banjarmasin. Random sampling was used, with a sample size of 64 respondents. Work Motivation and Organizational Culture are the independent factors, whereas employee performance is the dependent variable. Multiple Linear Regression Analysis, the F Test, and the t Test are used to prove the hypothesis.According to the study's findings, job motivation and organizational culture both have a substantial impact on employee performance. It is clear that Fcount (31.465) Ftable (3.15). Employee performance is influenced in part by work motivation and organizational culture. Work Motivation (0.004) (0.005) and t count (3.069) (1.999), organizational culture (0.003) (0.005) and t count (2.870) may be variables (1.999). Keywords: Work Motivation, Organizational Culture, and Employee Performance